Efficacy of a 20:1 CBD:THC cannabis herbal extract for pain and inflammation in dogs following tibial plateau leveling osteotomy - Lyons, Chloe; Pinto, K. Romany; Penney, Kira; Holmes, Laura; Salama, Abdul; Alcorn, Jane; Chicoine, Alan (Frontiers in Veterinary Science, 2025)
ObjectiveThis study investigates the efficacy of 20:1 cannabidiol:tetrahydrocannabinol (CBD:THC) cannabis herbal extract (CHE) in reducing pain and improving mobility in dogs undergoing tibial plateau leveling osteotomy (TPLO) for cranial cruciate ligament rupture (CCLr).MethodsForty-eight dogs were enrolled in a randomized, double-blinded, placebo-controlled clinical trial at the Western College of Veterinary Medicine between December 2022 and October 2024. Dogs were assigned to one of the three treatment groups: placebo (flavored olive oil), 2 mg CBD (0.1 mg THC)/kg body weight (bw), or 5 mg CBD (0.25 mg THC)/kg bw. All dogs received a standard peri- and post-operative analgesic protocol consisting of opioids, nerve blocks, non-steroidal anti-inflammatory drugs (NSAIDs), and gabapentin. Veterinary assessments were performed on days +1 and +14 postoperatively and included Glasgow Composite Pain Scores (GCPS), stifle range of motion (ROM), thigh and stifle circumference, and gait symmetry ratios. Owners were advised to complete a modified Canine Brief Pain Inventory (CBPI) on days +3, +7, and +14. Plasma cannabinoid concentrations on days 1 and 14 were analyzed using liquid chromatography–tandem mass spectrometry (LC–MS/MS). Data were analyzed using linear mixed models and generalized estimating equations.ResultsForty-two dogs completed the study. All dogs had marked improvement in owner-reported pain scores from days +1 to +14, regardless of treatment group. There were no significant differences in outcome measures between treatment groups. Potential treatment × day interactions were noted for ROM and gait symmetry; the high CHE dose group had marginally greater function on day +1, but none of these effects persisted to day +14. No serious adverse events were reported; mild gastrointestinal effects (vomiting or diarrhea) were noted in seven cases. Owners reported the CHE doses were generally well tolerated. Plasma cannabinoid concentrations were highly variable and did not correlate with clinical outcomes.Clinical significanceOverall, administration of an oral 20:1 CBD: THC cannabis herbal extract in addition to a standard analgesic protocol did not improve analgesia and limb function following TPLO surgery in dogs. Minor functional benefits may have occurred in the higher CHE dose group, but only on the first day following surgery. Current multimodal peri- and post-operative analgesic practices were effective, irrespective of CHE administration.